What is The Comparative Effectiveness of Dual Antibiotic Therapy Versus Monotherapy in Treating Uncomplicated Gonococcal Infections in Adults? : A Systematic Review - Ade Putri; Dita Titis Parameswari; Shania Rizky Amalia; Diandra Erieka Putri; Vinzia Ethiofia Caneabung (International Medical Journal Corp. Ltd, 2025)
Introduction: The treatment of uncomplicated gonococcal infections, caused by Neisseria gonorrhoeae, is challenged by increasing antimicrobial resistance. The failure of monotherapies prompted a shift to dual antibiotic therapy, with ceftriaxone plus azithromycin established as the standard of care. However, emerging resistance concerns necessitate the evaluation of alternative regimens. This systematic review aims to assess the comparative effectiveness of dual antibiotic therapy versus monotherapy and compare various dual-therapy combinations for treating uncomplicated gonorrhea in adults. Methods: This review adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. A systematic search of PubMed, Springer, Semantic Scholar, and Google Scholar was conducted using a PICO framework to identify relevant studies published since 2015. Eighteen studies, including randomized controlled trials and systematic reviews, met the inclusion criteria. Data on study design, treatment regimens, population characteristics, cure rates, and adverse effects were extracted and synthesized. Results: Dual therapy was found to be decisively superior to monotherapy, with one study reporting a 17.8% failure rate for cephalosporin monotherapy versus 0% for dual therapy. The combination of ceftriaxone plus azithromycin consistently achieved the highest cure rates, ranging from 98% to 100%, across genital, rectal, and pharyngeal sites. The alternative regimen of gentamicin plus azithromycin yielded mixed results; while some trials showed non-inferiority, a large trial reported lower efficacy (91% vs. 98%) and was particularly less effective at extragenital sites. Adverse events were typically mild, with gastrointestinal issues being most common. Discussion: The synthesized evidence confirms that dual therapy is essential for the effective treatment of gonorrhea. Ceftriaxone-based combination therapy remains the benchmark due to its high and consistent efficacy. Alternative regimens, particularly those using gentamicin, should be considered second-line options and used with caution, given their lower cure rates for pharyngeal and rectal infections. Conclusion: Ceftriaxone-based dual therapy is the most dependable strategy for treating uncomplicated gonorrhea. The choice of therapy must be guided by site-specific efficacy and local resistance data. Continuous surveillance and research into new agents are critical to address the ongoing threat of antimicrobial resistance.